Tecnologia ambiental na gestão de recursos naturais: o “voo” tecnológico da fiscalização mineral do estado do Pará - SAMPAIO FILHO, Inaldo de Sousa (Universidade Federal do Pará, 2017)
The technology features of unmanned aerial vehicles (UAVs) potentiate its civil use in several areas. Glimpsing the potential use in mineral inspection area of this technology, it was acquired by the federal competence agency in the granting and mineral inspection of Pará State. However, the availability and the fact to acquire such technology are not sufficient for success in their use. The success or failure is directly related to the way that this technology is managed. This research aimed to analyze the process of incorporating this technology as mineral inspection tool by the National Mineral Production Department of Pará State (DNPM-PA). For this purpose, used methodological approach based on technological innovation management processes of Nuchera, COTEC Foundation and Tidd and Bessant. About the research procedures, bibliographical and documentary surveys were conducted, interviews and application of free questionnaires for case study. The research development showed that, despite the potential of UAVs as mineral inspection tool, the technology is not getting incorporated strategically of Pará State. Stands out that the inspection is a fundamental part in the natural resources management, acting on the control and monitoring of environmental impacts from the mining activity, and that the spread of this technology will contribute to the strengthening of inspection activities in the state, since the insertion of UAVs is performed within the technological innovation management concepts.